RECOGNITION OF THE EXTENDED-SPECTRUM-Β-LACTAMASES (ESBLS) AMONGST THE GRAM-NEGATIVE BACTERIA ISOLATED FROM BURN WOUND INFECTION: Pharmaceutical Sciences-Biotechnology - YEKTAMOGHADDAM, NILOUFAR; REZA ARIAEE, AHMAD; DAVOUDI, NOUSHIN (International Journal of Life Science and Pharma Research, 2022)
Burn wound infections have caused high rate of death. Gram negative bacteria such as Pseodomonas auranginosae and Acinetobacteria have been reported as one of the most important bacteria involving in the infections. Besides, different level of resistance to beta-lactam antibiotics have been observed amongst the bacterial strains. Accordingly, the aim of this study was to phenotypically detect the resistance isolates and determine the genes encoding the ESBLs including tem, shv, and ctx-m amongst the resistance isolates at Motahari hospital (Tehran, Iran) by polymerase chain reaction (PCR). Eighty-two isolates were isolated from patients at different wards during 6 months. They were identified as P. auranginosae and Acinetobacter using biochemical tests. The phenotypic confirmatory test was used to screen the isolates for production of ESBLs. Susceptibility of isolates to 6 different antimicrobial agents was determined using agar disk diffusion method. To amplify the tem, shv, and ctx-m the template DNA was extracted by boiling method. Plasmid DNA was extracted using mini preparation kit and used as template in PCR for detection of tem, shv, and ctx-m. The phenotypic confirmatory assay detected 55 isolates showing resistance against the antibiotics. The rates of resistance to different antibiotics were in the following order: gentamycin (82.75%), amikacin (84.5%), tetracycline (98.2%), ciprofloxacin (88%), ceftriaxone (90%), and ceftizoxime (96.5%). Fifty-five strains harbored the resistance genes so that 31 and 10 isolates had ctx and tem genes respectively while presence of shv gene was not detected amongst the isolates. It appears that TEM, CTX enzymes are the dominant ESBLs among the resistant strains of P. auranginosae and Acinetobacteria in Iran.